2020
DOI: 10.1155/2020/8876125
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Mucormycosis: An Infection of Fungal Invasion into the Gastric Mucosa in Immunocompromised Patients

Abstract: Primary gastric mucormycosis is a rare but potentially lethal fungal infection due to the invasion of Mucorales into the gastric mucosa. It may result in high mortality due to increased risk of complications in immunocompromised patients. Common predisposing risk factors to develop gastric mucormycosis are prolonged uncontrolled diabetes mellitus with or without diabetic ketoacidosis (DKA), solid organ or stem cell transplantation, underlying hematologic malignancy, and major trauma. Abdominal pain, hematemesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In 2020, Haider et al reported a case of gastric mucormycosis complicated by mucosal invasion in a patient with poorly controlled diabetes and chronic renal disease, confirmed by histopathologic examination, PCR and culture of the biopsy specimens detecting Rhizopusmicrosporus DNA. 5 Chow et al reported a case of gastric angioinvasive mucormycosis in 2017, as a deadly complication in immunocompromised patient after penetrating trauma. 6 A rare case of gastric mucormycosis complicated with gastropleural fistula was reported by Tomohisa et al in a 82 years old female on immunosuppressives for adult onset Still's disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, Haider et al reported a case of gastric mucormycosis complicated by mucosal invasion in a patient with poorly controlled diabetes and chronic renal disease, confirmed by histopathologic examination, PCR and culture of the biopsy specimens detecting Rhizopusmicrosporus DNA. 5 Chow et al reported a case of gastric angioinvasive mucormycosis in 2017, as a deadly complication in immunocompromised patient after penetrating trauma. 6 A rare case of gastric mucormycosis complicated with gastropleural fistula was reported by Tomohisa et al in a 82 years old female on immunosuppressives for adult onset Still's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Newer therapies for mucormycosis include posaconazole and deferiprone and adjunctive hyperbaric oxygen therapy. 5,6…”
Section: Discussionmentioning
confidence: 99%
“…CT of the abdomen has non-specific signs such as ulceration, mucosal thickening, or intramural mass lesion. Endoscopy usually reveals variably sized and numbered mucosal ulceration with green to black exudates with or without necrosis of the tissue [10]. Imaging of paranasal sinuses and brain shows mucosal thickening of sinuses, soft tissue density in paranasal sinuses extending into orbit and brain, brain abscess, ring-enhancing lesions, infarcts, and cavernous sinus thrombosis [11].…”
Section: Discussionmentioning
confidence: 99%
“…The presenting symptoms of GI mucormycosis vary, and the most common one is abdominal pain. Nausea, vomiting, hematemesis, hematochezia, and melena are the other clinical manifestations of the disease (5). The mortality after GI involvement is often due to perforation, peritonitis, and GI bleeding (1).…”
Section: Discussionmentioning
confidence: 99%